The Effect of Psychological Contract Breach on Organizational Silence: The Moderating Effect of Psychological Capital - Atılhan Naktiyok; Fatma Merve Durdağ (Journal of Economy Culture and Society)
The aim of this study was to investigate the role of psychological capital in the relationship between perceptions of psychological contract breach and organizational silence. According to the results of the analysis, changes in psychological capital play an important role in the effect of psychological contract breach perception on defensive silence. Additionally, the sample was divided into 3 clusters according to psychological capital levels through cluster analysis to determine the regulatory effects of psychological capital. For each cluster, the effects of psychological contract breach perception on the independent variables of acquiescent, defensive, and prosocial silence were examined. As a result of the cluster analysis, it was observed that psychological contract breach perception caused a significant decrease in all types of silence (acquiescent, defensive, and prosocial) for the group with medium-level psychological capital. Psychological contract breach perception (PCB) at all capital levels (high, medium, and low) has been shown to reduce prosocial silence. These findings provided valuable information about psychological capital and its level, which is a unique resource for organizations.